Pengaruh Diversitas Gender dan Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Pemoderasi Modal Intelektual pada Emiten Sub PRoperty dan Real Estate 2018-2022 - Maghfirah, Ana; Ika Prajawati, Maretha (Indonesian Journal of Islamic Economics and Business, 2023)
This study focuses on Intellectual Capital as a moderator of Gender Diversity and Firm Size on Firm Value. The aim of this study is to look at the effect of gender diversity and company size moderated by intellectual capital on company value in the property and real estate sub-sector listed on the Indonesia Stock Exchange in 2018-2022. The type of research used is quantitative. The population in this study is real estate property companies listed on the Indonesia Stock Exchange in 2018-2022. In this study, there were 40 companies that were sampled based on the sampling criteria set by the researcher. The data collection analysis method uses descriptive statistical analysis and moderated regression analysis (MRA) using Statistical Product and Service Solutions (SPSS) Software. The results of this study indicate that gender diversity and firm size have a significant effect on firm value. Meanwhile, intellectual capital as measured using the Value Added Intellectual Coefficient (VAICTM) can strengthen the relationship between gender diversity and company value. Meanwhile, the size of companies with intellectual capital is not able to moderate the value of the company.